Papua New Guinea Education Management Information System : SABER Country Report 2015 - World Bank Group (World Bank, Washington, DC, 2015)
In 2011, the World Bank Group commenced a multiyear program designed to support countries in systematically examining and strengthening the performance of their education systems. By leveraging this global knowledge, the systems approach for better education results (SABER) tools fill a gap in the availability of data and evidence on what matters most to improve the quality of education and achievement of better results. This report discusses the results of applying the SABER - education management information systems (EMIS) tool in Papua New Guinea (PNG). The objectives of this report are to examine the system according to key policy areas, identify successes and challenges in the system, and provide recommendations to support the continued advancement of EMIS in PNG. A successful EMIS is credible and operational in planning and policy dialogue as well as teaching and learning.